Man as a “Work of Art”: The Religious–Dialogical Dimension of Education as a Path of Education for Beauty/Goodness - Razum, Ružica (Religions, 2023)
Aiming to establish a dialogue with modern man, who lives in a culture marked by great challenges, church documents put a great emphasis on the via pulchritudinis. The via pulchritudinis, i.e., the way of beauty, is considered to be a privileged way of achieving dialogue. Awareness of the importance of beauty, in close connection with goodness and truth, is increasingly present in the theological and the religious–pedagogical thought. One of the specific questions related to education for beauty refers to the education of a person who is called to transform his or her life into a “work of art”. This paper reflects on only one specific aspect of the issue of shaping human beauty/goodness, that is, people’s “humanity”, in connection with the challenges of increasingly complex coexistence in diversity. Globalization and migration trends, primarily by complicating life together/coexistence, pose certain challenges to man as an individual, as well as to the entire society, especially the challenge that is coexistence of different cultures and religions. Since these problems also penetrate school classrooms, education systems are expected to provide appropriate responses. The paper consists of two parts. In the theoretical part, two specific fundamental issues related to the education of a person’s “humanity” in the atmosphere of “conflict culture” are considered: the issue of comprehensive education following the ancient connection of beauty and goodness, as well as the issue of education for coexistence. The second part presents the results of the research which was carried out in the Republic of Croatia and which aimed to examine the presence of curriculum content that enables the acquisition of religious–dialogical competence, using the method of text analysis. In more exact terms, faced with the challenges that arise from a society burdened with misunderstanding, violence and hostility, often linked with a religious affiliation and worldviews, we ask ourselves the following question: to what extent is the contemporary education system in the Republic of Croatia, at the level of its curricula, open to the comprehensive development of students, especially in terms of the development of the religious–dialogical dimension, necessary for living a good and beautiful life in the modern multicultural and multireligious world? The results reveal a different, mostly insufficient, openness of the curriculum to the religious dimension of intercultural education. That is one of the reasons why the education system does not seem to be open to the development of the knowledge, attitudes and skills necessary for a harmonious and “beautiful” coexistence in modern society.